PENGARUH PAJAK DAERAH DAN RETRIBUSI DAERAH TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI KOTA PADANG SETELAH DIKELUARKANNYA UNDANG-UNDANG OTONOMI DAERAH - Halkadri Fitra (Jurnal Praktik Bisnis, 2016)
The purpose of this study was to determine the effect of local taxes on revenue, and to determine the influence of local retributions on revenue as well as to determine the effect of local taxes and local retributions together on revenue. The research was conducted in the city of Padang using secondary data from 2000 to 2014 and classified as descriptive research. Based on the results of data processing, it can be seen that the regression model there is no irregularity in the classical assumption test. Then, based on the results of t test analysis found that local taxes have a positive and significant impact on revenue. Then local retribution also have a positive and significant impact on revenue. And to influence together through F test, it is known that local taxes and local retributions together have a positive and significant impact on revenue. Keywords: local taxes, local retribution, local revenue